Trends in the Development of Vocational Education and Training Research Studies in Southeast Asia - Usup; Supriyono; Hardika; Dayati, Umi (JTP - Jurnal Teknologi Pendidikan, 2024)
This study examines the development trends of vocational training research studies in Southeast Asia in the period 2014 to 2024 using bibliometric analysis methods. By setting the keyword "vocational training in Southeast Asia," this study collected data from academic databases and produced 1500 relevant journals. After going through the screening process, 844 articles were obtained which were then analyzed to identify trends and patterns in vocational training. The results of the analysis show three main phases: the initial phase (2014–2018) which focuses on aspects of psychology and political science; the development phase (2019–2021) which highlights the importance of physical and mental health; and the mature phase (2022–2024) which shifts attention to the social and economic impacts of vocational training. In addition, this study shows fluctuations in the number of publications, with a significant peak occurring in 2020. Singapore, Thailand, and Malaysia dominate research contributions in this region. The main topics covered include competencies and skills, learning and curriculum, industry partnerships, policies and implementation, and technology and innovation. These findings provide a comprehensive picture of the evolution of thinking in vocational training in Southeast Asia, and suggest further research directions to strengthen the integration between vocational education and industry needs.